A Demonstration of a Simple Methodology of Flood Prediction for a Coastal City Under Threat of Sea Level Rise: The Case of Norfolk, VA, USA. Issue 9 (26th September 2022) - Ezer, Tal
Abstract: Many coastal cities around the world are at risk of increased flooding due to sea level rise (SLR), so here a simple flood prediction method is demonstrated for one city at risk, Norfolk, VA, on the U.S. East Coast. The probability of future flooding is estimated by extending observed hourly water level for 1927–2021 into hourly estimates until 2100. Unlike most other flood prediction methods, the approach here does not use any predetermined probability distribution function of extreme events, and instead a random sampling of past data represents tides and storm surges. The probability of flooding for 3 different flood levels and 3 different SLR projections are calculated, and the results are consistent with more sophisticated methods. Under intermediate‐low SLR projection an empirical formula is found to estimate the lower bound of flooding time, showing that water level that exceeds the high tide (Mean Higher High Water, MHHW) occurred ∼0.3% of the time in the 1960s, increased to ∼6% in 2021, and projected to occur 100% of the time by ∼2080. Under intermediate SLR projection, 1000 simulations of the probability of maximum annual water level were conducted, showing that storm surges may reach ∼2 m over MHHW by 2050 and ∼3 m over MHHW by 2100; in comparison, storm surges in Norfolk over the past 90 years reached 1.6 m only once. The method derived here could be adopted to other locations and help planning mitigations and adaptation strategies for cities at risk. Plain Language Summary: Like many coastal cities around the world, Norfolk, VA, on the U.S. East Coast is experiencing accelerated flooding. Therefore, this study estimates the probability of future flooding in the city using a simple method that combines sea level rise projections with the impacts of tides and storm surges. An empirical relation is found to estimate the percentage of time the city is flooded for any flood level and any year from 1960 to 2100. The results show for example, that major floods that occurred very rarely in the past 90 years may occur almost daily to weekly by 2100, and the largest storm surges that in the past rarely reached 1.5 m over the high tide may reach up to 3 m in the future. The method derived here could be adopted to other locations and help planning mitigations and adaptation strategies for cities at risk. Key Points: The impact of sea level rise (SLR) on accelerated minor tidal flooding and increased frequency of storm surges is demonstrated in Norfolk, VA A simple method predicts the probability of future floods from the combined impact of SLR, tides, and storm surges Major floods that in the past 90 years were very rare, will become weekly to daily events by 2100